Short-Term Effects of Supplemental L-Arginine, Diosmin, Troxerutin, and Hesperidin in Diabetic Patients: A Pilot Study. (2nd December 2021) - Bagnati, Marco; Puricelli, Chiara; Bauce, Giulia; Basile, Matteo; Grigollo, Barbara; Prodam, Flavia; Dianzani, Umberto; Bellomo, Giorgio; Rolla, Roberta
Abstract : Background and Aims . Inflammatory, oxidative stress, and endothelial dysfunction play a key role in the pathogenesis of long-term cardiovascular complications in patients with diabetes. The present observational prospective study is aimed at evaluating the effects of micronutrients and phytochemicals contained in the dietary supplement Flebotrofine® (AMNOL Chimica Biologica) on biochemical markers of inflammation, endothelial dysfunction, and glycemic control in patients with diabetes. Methods . 105 type 1 or type 2 diabetes patients regularly took a daily dose of the dietary supplement Flebotrofine® for three consecutive months, and haematological and biochemical parameters were checked at baseline, after three months of treatment, and one month after its suspension. Statistical comparison of the laboratory parameters was performed using the two-tailed ANOVA test for repeated samples with a statistical significance level set at p < 0.05 . Results . The daily use of Flebotrofine® did not change the glycemic metabolic compensation of enrolled patients. After three months of regular Flebotrofine® intake, the plasma levels of the antioxidant β -carotene and of arginine were significantly higher compared with the baseline values, with a decrease in the ADMA/arginine ratio. In contrast, apolipoprotein B, ApoB/ApoA1 ratio, and platelet and leukocyte counts significantly dropped. Conclusion . The daily use of Flebotrofine® might be a valid supplement of arginine, the precursor of NO, and essential in the prevention of endothelial dysfunction. The regular intake of arginine and phytochemicals also improved the antioxidant and antithrombotic profile of enrolled patients. Therefore, Flebotrofine® could be a useful dietary supplement to prevent long-term complications in patients with diabetes.